Analysis and Implementation of Microservice Architecture Related to Patient Drug Schedule Based on FHIR Standard - Ariq Musyaffa Ramadhani; Andrian Rakhmatsyah; Rahmat Yasirandi (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2021)
In several previous studies, smart devices have been developed to help improve a patient's medication adherence but have problems, namely data management that is not centralized and not integrated, so that mitigation is quite vulnerable. In this study, a platform was built that can manage data centrally and apply the FHIR (Fast Healthcare Interoperability Resources) health data standard. The main components used to implement the FHIR standard are resources and REST APIs. The resource is a data model that defines the structure and data elements that are exchanged. This data exchange is carried out on top of the REST API using the HTTP protocol. Platform testing uses positive/negative testing and stress testing methods to be able to see the performance of the platform. The test results show that the platform prototype can provide a response that is in accordance with the request given and has a very tolerant error value of 0% with a latency value of 3 to 22 seconds with a total of 100 to 130 users.